Temporal Regulation of Interleukin-12p70 (IL-12p70) and IL-12-Related Cytokines in Splenic Dendritic Cell Subsets during Leishmania donovani Infection - Maroof, Asher (American Society for Microbiology (ASM), 2008)
Dendritic cells (DC) play an essential role in initiating and directing T-cell responses, in part by production of interleukin-12p70 (IL-12p70), IL-23, and IL-27. However, comparative studies on the capacity for cytokine production of DC subsets are rare. Here, we compare splenic CD8α(+), CD4(+), and double-negative (DN) DC, isolated 5 h to 28 days after Leishmania donovani infection, for (i) production of IL-12p70, (ii) accumulation of IL-12/23p40, IL-12p35, IL-23p19, and IL-27p28 mRNAs, and (iii) their capacity to direct CD4(+) T-cell differentiation. At 5 h, conventional DC (cDC) accumulated mRNA for IL-12/23p40 (CD8α>CD4>DN), IL-23p19 (CD4>CD8α>DN), and IL-27p28 (CD8α>CD4>DN), in an infection dose-dependent manner. IL-12p70 was restricted to CD8α(+) cDC, reflecting the subset-specific accumulation of IL-12p35 mRNA. In contrast, cDC from mice infected for 14 to 28 days accumulated little mRNA for IL-12p40 and IL-12p19, though IL-27p28 mRNA remained detectable (CD8α>DN>CD4). IL-12p70 secretion by CD8α(+) cDC was also absent, reflecting deficient IL-12/23p40, rather than IL-12p35, mRNA accumulation. The capacity of CD8α(+) cDC isolated early after infection to direct Th1 cell differentiation was mediated through IL-12/23p40, whereas this ability in CD4(+) and DN cDC was independent of IL-12/23p40 and did not result from overexpression of Delta 4 Notch-like ligand. However, DN cDC produced gamma interferon (IFN-γ) and also contained a rare population of CD11c(hi) DX5(+) IFN-γ-producing cells. Our data illustrate the extensive diversity in, and temporal regulation of, splenic cDC subsets during infection and suggest caution in interpreting data obtained with unfractionated or minimally purified DC.